Optimizing Municipal Solid Waste Management through TPS 3R and Landfill Mining Integration: A Study from Kemang Final Disposal Site - Tengku Annisa Tsania; Christia Meidiana; Imma Widyawati Agustin (Civil and Environmental Science Journal (CIVENSE), 2025)
Rapid urban growth and increasing waste generation in Pangkalan Kerinci have intensified pressure on the Kemang Final Disposal Site, which is nearing full capacity. To address this issue, an integrated approach combining TPS 3R (Reduce, Reuse, and Recycle) and landfill mining was proposed. This study aimed to analyze the relationship between the integration of TPS 3R and landfill mining and its effect on extending landfill operational life. The novelty of this research lies in presenting the first integrated evaluation of TPS 3R and landfill mining in Indonesia, assessing their combined efficiency in reducing waste volume and prolonging landfill lifespan. The research utilized mass balance analysis and scenario modeling to compare three different strategies: (1) no intervention, (2) TPS 3R implementation, and (3) TPS 3R combined with landfill mining. Results showed that the application of TPS 3R alone reduced landfill input by 73.32 percent, extending its lifespan to 650 days. The most optimal outcome was observed in the third scenario, in which two screening units were used during landfill mining to reclaim sufficient space within 410 working days. This duration coincides precisely with the period when the active landfill cell reaches full capacity. The integration ensures service continuity, supports circular economy practices through the recovery of Refuse-Derived Fuel (RDF), and offers a replicable framework for sustainable solid waste management in similar urban contexts.